Klinefelter syndrome and cutaneous localization of diffuse large B cell lymphoma: a real connection or a casual association? - Federica Scarfì; Elisabetta Magnaterra; Simone Santini; Franca Taviti (PAGEPress Publications, 2023)
Diffuse large B cell lymphoma (DLBCL) is a frequent aggressive subtype of non-Hodgkin lymphoma, representing nearly 30-40% of all cases. The skin may be affected by the disease either primarily or secondarily. Herein we report a clinical and dermoscopic case of skin metastasis of DLBCL in a patient with Klinefelter Syndrome.